Challenges to Journal Editorial Work in West - Africa: Lessons from the University of Ghana - Oppong Bekoe, Emelia; Kilbertson Zuttah, Jacob; Mawuena A., Abortta; Adjei- Mensah, Tom Dockery; Mills, David (Ghana Library Journal, 2025)
Journals are the main outlets for accurate and quality research dissemination, but many in developing countries are fraught with peculiar challenges. This article outlines challenges faced by journal editors from the University of Ghana. Challenges include transitioning to digital platforms, understanding the review process, copyediting, website updates, production, indexing issues, proofreading, among others. Specific topics of interest included addressing plagiarism, utilizing AI in editorial work, effectively recruiting and managing reviewers, and insights on journal indexing. Additionally, they emphasized the dire need for institutional support in journal management towards the establishment of an editorial office, a university journal management policy, mentorship, increased opportunities for networking, continual professional training, and the availability of IT support staff etc. to ensure sustainability. This study brought out the prevalent hurdles that many editors within Ghana, and the sub-region daily encounter in their work and the need for support.